THE CORRELATION OF ENDOSCOPIC AND ULTRASONOGRAPHIC FINDINGS IN PATIENTS WITH PORTAL HYPERTENSION - Osman ONAT; Selami SERHATLIOĞLU; Ali DEMİR and Emir DÖNDER and Oğuz AYHAN and Reşat ÖZERCAN and Ahmet YILDIRIM (Turkish Journal of Gastroenterology, 2020)
-